Development of Java Hands Startup Business Idea Model by Lean Startup Approach - Alwiyah; Watini, Sri (Pandawan Sejahtera Indonesia, 2023)
Exporting is one of the activities that help increase a country's foreign exchange income. However, there are still many export commodities that have not been maximized. One of them is handicrafts. Java Hands is an e-commerce company aiming to sell handicrafts made by Yogyakarta artisans to overseas markets. Based on the observations made, there are fluctuations in the value of Indonesia's handicraft exports. Only one country controls the value of exports. Java Hands aims to increase interest in crafts and help artisans find new markets. The Java Hands build process is designed with a lightweight startup approach. This approach makes work more efficient and faster. Lean Startup consists of three phases. This is market validation, product validation, business validation. After completing these three phases, your existing data will be analyzed and a prototype of your Java Hands application will be created.